2003
DOI: 10.1080/0309192031000114349
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Emission of Gravity Waves by Interacting Vortex Dipoles in a Stratified Fluid: Laboratory Experiments

Abstract: Results from a new series of experiments on the geophysically important issue of spontaneous emission of internal gravity waves during unsteady interactions of vortical structures are presented. Vortex dipoles are a common element of a quasi-two-dimensional turbulent flow. Vortex dipoles perform translational motion and can collide with other vortices. During collision events the flow is unsteady and unbalanced and a further adjustment process associated with these events can therefore result in the spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…In this case the energy transfer is (100 ϫ ⌬E T )/(⌬tE T ) Ӎ 0.7%, or 7% per rotation period. The order of magnitude of these values are in agreement with the 4% estimated by Afanasyev (2003) after a dipole collision in laboratory experiments, and the 1% obtained by Williams et al (2007, manuscript submitted to J. Atmos. Sci.).…”
Section: The Averaged Horizontal Phase Speedsupporting
confidence: 86%
See 2 more Smart Citations
“…In this case the energy transfer is (100 ϫ ⌬E T )/(⌬tE T ) Ӎ 0.7%, or 7% per rotation period. The order of magnitude of these values are in agreement with the 4% estimated by Afanasyev (2003) after a dipole collision in laboratory experiments, and the 1% obtained by Williams et al (2007, manuscript submitted to J. Atmos. Sci.).…”
Section: The Averaged Horizontal Phase Speedsupporting
confidence: 86%
“…IGWs easily develop also when unbalanced initial conditions are used in numerical simulations (e.g., Daley 1991, chapter 6); meanwhile the unbalanced mass and momentum fields slowly adjust through geostrophic adjustment (Rossby 1938) or, more generally, any balance adjustment (Zhang 2004). Recently, several oceanographic and atmospheric studies (Ford 1994;Ford et al 2000;Afanasyev 2003;Lovegrove et al 2000;Plougonven and Zeitlin 2002;Williams et al 2003Williams et al , 2005Lane et al 2004;Viúdez and Dritschel 2006;Viúdez 2006) have shown that weak (in the horizontal velocity field) IGWs can be spontaneously emitted (i.e., in the absence of any external forcing like wind stress or bottom topography) from balanced or near-balanced, nonstationary flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of the flow regimes observed in the experiment is found in Hide & Mason (1975). Promising laboratory experiments on wave generation observed at the interface between two superposed fluids of differing density have been done by Lovegrove, Read & Richards (1999, Williams, Read & Haine (2003) and Williams, Haine & Read (2005 for a baroclinically unstable flow in the rotating annulus, and by Afanasyev (2003) for colliding vortex dipoles in a non-rotating experimental set-up. A variant of the conventional differentially heated rotating annulus, where, in addition to the horizontal temperature gradient, an external vertical temperature gradient is applied, is discussed by Hathaway & Fowlis (1986) and Miller & Fowlis (1986) and modelled by Kwak & Hyun (1992).…”
Section: Introductionmentioning
confidence: 98%
“…We discuss the consequences of this energy flux for the atmosphere and ocean in section 6. For comparison, Afanasyev (2003) estimates that approximately 4% of the energy is radiated as inertia-gravity waves in a nonrotating, linearly stratified laboratory fluid during the adjustment after the collision of two translating vortex dipoles.…”
Section: Energy Flux From Balanced Flow Into Inertia-gravity Wavesmentioning
confidence: 99%